LEGAL REGULATION OF EQUITY-BASED CROWDFUNDING (World Bulletin of Social Sciences, 2023)
Equity-based crowdfunding (EBC) has emerged as a significant alternative financing mechanism for startups and small businesses. This article delves into the legal regulations surrounding EBC, highlighting the balance regulators must strike between fostering innovation and ensuring investor protection.
Keywords: Equity-Based Crowdfunding; Legal Regulation; Investor Protection